Caracterização e classificação de resíduos sólidos em instituições de ensino superior: um estudo de caso no Centro de Ciências Exatas e Tecnologia da Universidade Federal de São Carlos - Pereira, Gabriela Alves (Universidade Federal de São Carlos, 2019)
More and more the society has been experiencing a developing process of awareness-raising through its environmental, social and even economic contexts, regarding the products and services used by the population. In this scenario, since the early nineties the Federal University of São Carlos (UFSCar) makes efforts to achieve a self-sustainability and of its surrounding environment. However, despite of the existence of some actions, the role of the higher education system as a player for an effective environmental awareness remains slow. Thus, the concept of continuous improvement takes place, in order to guarantee the continuity of the activities undertaken by the heads of environmental management and sustainability issues at the universities, as well as to encourage an ever-evolving local. The application of this concept represents the main goal of this work, which was focused on the processes of generation and discharge of solid wastes from academic departments of the Exact and Technology Sciences Center (CCET) of UFSCar, at the São Carlos campus. The research is classified as a study of case, with applied nature, and descriptive character. Interviews and questionnaires were applied to the people responsible for generating and discharging solid wastes. The analysis of the obtained data was used to point out an initial scenario of solid wastes occasioned by the studied Academic Center. Furthermore, it was possible to provide an overview of the major features related to the producing sources and the management processes for these materials. Altogether, the identification of significant problematic aspects discussed here leads to need of training programs and new projects to promote new social-environmental believes and proper behavior inside the academic community, in order to make the university an example for environmental matters to its society.
Characterization and classification of solid waste in higher education institutions: a case study at the Centro de Ciências Exatas e Tecnologia da Universidade Federal de São Carlos
Keywords: Sustentabilidade; Gestão de resíduos; Melhoria contínua; IES; Sustainability; Waste management; Continuous Improvement; HEI; ENGENHARIAS::ENGENHARIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS